Hypoxia-induced apoptosis of cardiomyocytes is restricted by ginkgolide B-downregulated microRNA-29. Issue 10 (18th May 2020) - Ren, Dezhi; Li, Fang; Gao, An; Cao, Qingwen; Liu, Yarong; Zhang, Junru
ABSTRACT: Ginkgolide B exerts a cardioprotective function against ischemia-caused apoptosis in myocardial infarction. Here we sought out to address a functional mechanism associated with microRNA-29 (miR-29). Rat cardiomyocytes (H9c2 cells) were cultured in ginkgolide B-conditioned medium prior to hypoxic induction. To construct miR-29-overexpressed cells, miR-29 mimic was transfected into H9c2 cells. The cells were harvested for assaying survivability and apoptosis by CCK-8 and FITC-Annexin V staining methods. Western blot was applied to identify apoptotic hallmarks and signaling transducers. RT-PCR was carried out for investigating miR-29 expression. Cardiomyocytes were sensitive to hypoxic apoptosis, while ginkgolide B intensified the abilities of cardiomyocytes to resist hypoxia by increasing survivability and repressing apoptosis. Specifically, ginkgolide B repressed Bax and cleaved caspase 3 while enhanced Bcl-2. Ginkgolide B buffered the expression of miR-29 induced by hypoxia. However, ginkgolide B showed a slight role in survivability and apoptosis in the cells overexpressing miR-29. Meanwhile, ginkgolide B triggered the phosphorylation of PI3 K and AKT, as well as induced Sp1, while this beneficial role was abrogated in the cells treated by miR-29 mimic. Our results confirmed that ginkgolide B might have therapeutic significance by repressing hypoxic apoptosis. Ginkgolide B-elicited miR-29 inhibition might be the basis of this beneficial role.